Anti-Neurofascin 155 Antibody-Positive Chronic Inflammatory Demyelinating Polyneuropathy/Combined Central and Peripheral Demyelination: Strategies for Diagnosis and Treatment Based on the Disease Mechanism - Kira, Jun-ichi (Frontiers in Neurology, 2021)
Chronic inflammatory demyelinating polyneuropathy (CIDP) is an immune-mediated demyelinating disease of the peripheral nervous system (PNS). A small number of CIDP patients harbor autoantibodies against nodal/paranodal proteins, such as neurofascin 155 (NF155), contactin 1, and contactin-associated protein 1. In most cases, the predominant IgG subclass is IgG4. Node/paranode antibody-positive CIDP demonstrates distinct features compared with antibody-negative CIDP, including poor response to intravenous immunoglobulin. Neuropathology of biopsied sural nerve shows Schwann cell terminal loop detachment from axons without macrophage infiltration or inflammation. This is partly attributable to IgG4, which blocks protein–protein interaction without inducing inflammation. Anti-NF155 antibody-positive (NF155+) CIDP is unique because of the high frequency of subclinical demyelinating lesions in the central nervous system (CNS). This is probably because NF155 coexists in the PNS and CNS. Such cases showing demyelinating lesions in both the CNS and PNS are now termed combined central and peripheral demyelination (CCPD). NF155+ CIDP/CCPD commonly presents hypertrophy of spinal nerve roots and cranial nerves, such as trigeminal and oculomotor nerves, and extremely high levels of cerebrospinal fluid (CSF) protein, which indicates nerve root inflammation. In CSF, CXCL8/IL8, IL13, TNFalpha, CCL11/eotaxin, CCL2/MCP1, and IFNgamma levels are significantly higher, and IL1beta, IL1ra, and GCSF levels are significantly lower in NF155+ CIDP than in non-inflammatory neurological diseases. Even compared with anti-NF155 antibody-negative (NF155−) CIDP, CXCL8/IL8 and IL13 levels are significantly higher, and IL1beta and IL1ra levels are significantly lower than in NF155+ CIDP. Canonical discriminant analysis revealed NF155+ and NF155− CIDP to be separable with IL4, IL10, and IL13 the three most significant discriminators, all of which are required for IgG4 class switching. Therefore, up-regulation of both Th2 and Th1 cytokines and down-regulation of macrophage-related cytokines are characteristic of NF155+ CIDP, which explains spinal root inflammation and lack of macrophage infiltration in the sural nerves. All Japanese patients with NF155+ CIDP/CCPD have one of two specific HLA haplotypes, which results in a significantly higher prevalence of HLA-DRB1*15:01-DQB1*06:02 compared with healthy Japanese controls. This indicates an involvement of specific HLA class II molecules and relevant T cells in addition to IgG4 anti-NF155 antibodies in the mechanism underlying IgG4 NF155+ CIDP/CCPD.